2007
DOI: 10.1038/sj.jp.7211764
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of morphine following surgery in neonates

Abstract: Objective: To determine the effect of morphine on duration of mechanical ventilation, apnoea and hypotension among full-term neonates who underwent thoracic or abdominal surgery in a level III neonatal intensive care unit.Method: Medical records of 82 infants were reviewed retrospectively and data including patient demographics, clinical diagnosis, type of surgery, postoperative opioid administration, duration of mechanical ventilation, hypotension, apnoea and pain scores (premature infant pain profile (PIPP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
0
12
0
1
Order By: Relevance
“…Because neonates are exposed to multiple painful procedures per day 13, 28 , previous investigations have focused on examining and decreasing the painful effects of these procedures. A number of interventions, such as the use of sucrose 1, 9, 27 , pacifiers 2, 9 , or morphine 3, 20 have been successful in decreasing signs of pain, but studies investigating the possible biochemical sequelae of painful procedures in neonates are needed. If exposure to multiple painful procedures is shown to contribute to oxidative stress, biochemical markers of such stress might be useful in evaluating mechanism-based interventions that could decrease the adverse effects of exposure to these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Because neonates are exposed to multiple painful procedures per day 13, 28 , previous investigations have focused on examining and decreasing the painful effects of these procedures. A number of interventions, such as the use of sucrose 1, 9, 27 , pacifiers 2, 9 , or morphine 3, 20 have been successful in decreasing signs of pain, but studies investigating the possible biochemical sequelae of painful procedures in neonates are needed. If exposure to multiple painful procedures is shown to contribute to oxidative stress, biochemical markers of such stress might be useful in evaluating mechanism-based interventions that could decrease the adverse effects of exposure to these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 62 ventilated term newborns found that postoperative morphine infusions prolonged the need for mechanical ventilation, but was not associated with apnea, hypotension, or other complications 123 . A series of RCTs comparing intermittent vs. continuous morphine infusions found that morphine is safe and effective for postoperative pain in term neonates and older infants 124-130 .…”
Section: Opioid Therapymentioning
confidence: 99%
“…Neonates, infants and children are often exposed to pain from invasive procedures during intensive care and during the post‐operative period (Pattinson and Fitzgerald, 2004). The use of opioid analgesia has increased in the Neonatal Intensive Care Unit (NICU) in the last decades as a consequence of the changes and advances in the understanding, identification, and treatment of pain in children (El Sayed et al, 2007). However, there is still a lack of knowledge on their specific effects in a long‐term administration for this population of patients (Marsh et al, 1997).…”
Section: Introductionmentioning
confidence: 99%